Experimental Study of the Efficacy and Safety of a New PEG-Based Laxative - E. V. Shekunova; E. V. Mazukina; V. A. Vavilova; V. V. Kashkin; V. Yu. Balabanyan; M. F. Fazylov; M. N. Makarova; V. G. Makarov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2022)
Bowel-cleansing PEG-based agents, including Moviprep®, are commonly used to prepare the large intestine for diagnostic examinations. PLNV-next is a newly developed fixed combination medicinal product with a composition similar to that of Moviprep®.The aim of the study was to estimate the pharmacological efficacy and toxicity of PLNV-next.Materials and methods: The study evaluated pharmacological efficacy of four formulations of PLNV-next in comparison with Moviprep® after a single administration in a therapeutic dose to outbred rats. The evaluation was carried out based on the laxative effect of the medicinal products. The authors recorded diarrhoea onset latency and the number of defecation boluses and diarrhoea spots produced during the 6-hour observation period. Toxicity of PLNV-next was studied in the formulation containing maximum amounts of the ingredients according to the patent. In the single-dose toxicity study, PLNV-next was administered intragastrically to rats at doses of 4.2 g/kg (maximum human therapeutic dose, MHTD), 21 g/kg (5 MHTD), and 42 g/kg (10 MHTD) and to ferrets at doses of 4.2 g/kg (MHTD) and 21 g/kg (5 MHTD). In the repeated-dose toxicity study, PLNV-next was administered for 14 days at 4.2 g/kg (rats and ferrets), 21 g/kg (5 MHTD, rats), and 12.6 g/kg (3 MHTD, ferrets). Additionally, the repeated-dose toxicity study evaluated safety pharmacology parameters for the cardio-vascular, respiratory and central nervous systems.Results: All PLNV-next formulations tested exerted a laxative effect equivalent to that of Moviprep®. No clinical signs of toxicity were observed in rats, with the exception of the laxative effect. Ferrets demonstrated decreased behavioral activity and diarrhoea. Nausea or emesis were noted in 75-90% of the ferrets receiving the doses exceeding the MHTD. A single administration of PLNV-next affected blood sodium concentrations: a slight increase was noted in the 5 MHTD and 10 MHTD groups of rats and in the 5 MHTD group of ferrets. The repeated-dose toxicity study in rats revealed a slight increase in sodium levels with both test doses. After a single administration of 5 MHTD to ferrets, the authors observed a decrease in potassium levels. All the changes were mild and within physiological ranges. PLNV-next toxic effects observed in the rat and ferret studies were similar to those reported in rat and dog toxicity studies of Moviprep®. Conclusion: PLNV-next exerts a marked laxative effect and has a favourable safety profile.